Screening for impaired renal function in outpatients before iodinated contrast injection: Comparing the Choyke questionnaire with a rapid point-of-care-test. Issue 7 (July 2015) - Too, C.W.; Ng, W.Y.; Tan, C.C.; Mahmood, M.I.; Tay, K.H.
Highlights: Iodinated intravenous contrast carries a low risk of contrast induced nephropathy (CIN). Patients with eGFR less than 45 mL/min/1.73 m 2 are particularly at risk for CIN. The Choyke questionnaire is used to screen for impaired renal function in outpatients. Choyke questionnaire is a good screening tool for eGFR less than 45 mL/min/1.73 m 2 . Point of care test (POCT) for serum creatinine can reduce waiting time. Abstract: Rationale and purpose: To determine the usefulness of the Choyke questionnaire with a creatinine point-of-care test (POCT) to detect impaired renal function amongst outpatients receiving intravenous iodinated contrast in a tertiary centre. Materials and methods: Between July and December 2012, 1361 outpatients had their serum creatinine determined by POCT and answered the Chokye questionnaire just before their examination. Results: Four hundred and eighty (35.2%) patients had at least one 'Yes' response. Forty-four patients (3.2%) had estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 and 14 patients (1.0%) have eGFR <45 mL/min/1.73 m 2 . Sensitivity, specificity, positive predictive value and negative predictive value of the Choyke criteria in detecting patients with eGFR <60 mL/min/1.73 m 2 are respectively: 65.9%, 65.8%, 6.0% and 98.3% and to detect eGFR <45 mL/min/1.73 m 2 : 92.9%, 65.3%, 2.7% and 99.9%. Only 'Yes' responses to 'Have you ever been told you have renal problems?' and 'Do you have diabetes mellitus?' were statistically significant in predicting eGFR <45 mL/min/1.73 m 2, with odds ratio 98.7 and 4.4 respectively. Conclusion: The Choyke questionnaire has excellent sensitivity and moderate-to-good specificity in detecting patients with <45 mL/min/1.73 m 2, below this level it has been shown that risk of contrast induced nephropathy increases significantly, making it an effective screening tool. Also the use of POCT can potentially reduce waiting time.